2022
DOI: 10.1080/21655979.2022.2068920
|View full text |Cite
|
Sign up to set email alerts
|

N6-methyladenosine (m6A) reader IGF2BP2 promotes gastric cancer progression via targeting SIRT1

Abstract: N 6 -methyladenosine (m 6 A) modification acts as the most prevalent internal modification in eukaryotic mRNA. Emerging evidence shows the critical biological roles of m 6 A key enzymes in human cancers. However, the roles of m 6 A binding protein IGF2BP2 in gastric cancer (GC) progression are still unclear. In this study, we confirmed that IGF2BP2 was highly expressed in GC cell lines and tumor tissues. Knocking down o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…IGF2BP1 promotes neuroendocrine tumor proliferation through post-transcriptional enhancement of EZH2 ( 21 ). N6-methyladenosine (m6A) reader IGF2BP2 encourages gastric cancer metastasis by targeting SIRT1 ( 22 ). By modulating SIRT1 in an m6A-dependent manner, the m6A methyltransferase KIAA1429 operates as an oncogenic factor in colorectal cancer ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…IGF2BP1 promotes neuroendocrine tumor proliferation through post-transcriptional enhancement of EZH2 ( 21 ). N6-methyladenosine (m6A) reader IGF2BP2 encourages gastric cancer metastasis by targeting SIRT1 ( 22 ). By modulating SIRT1 in an m6A-dependent manner, the m6A methyltransferase KIAA1429 operates as an oncogenic factor in colorectal cancer ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, it was revealed that VIM-AS1 was located in both the cytoplasm and the nucleus of prostate cancer cells and could directly interact with the IGF2BP2 protein. Previous studies have demonstrated that IGF2BP2 was both an important RNA-binding protein and an m6A reader (54,55). Numerous studies have indicated that IGF2BP2 could enhance mRNA stability by recognizing m6A modification sites (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…The study on colorectal cancer revealed that LncRNA LINRIS enhanced the stability of IGF2BP2, which increased the binding of IGF2BP2 to m 6 A-modified MYC [ 35 ]. Recent studies showed that IGF2BP2 promotes GC progression by targeting IGF1R and SIRT1 mRNAs and found that there are m 6 A modification sites on IGF1R and SIRT1 genes through bioinformatics analysis, so it is speculated that this promotion of IGF2BP2 may be mediated through m 6 A modification [ 36 , 37 ]. However, it is still unknown whether an m 6 A modification on HMGA1 mRNA was absolutely necessary for IGF2BP2 to regulate its expression.…”
Section: Discussionmentioning
confidence: 99%